Numerical simulation on lateral collapse of bamboo foam composite in hollow cylindrical tube subjected to quasi static loading - Noor, Noor Ekmal Hakim Bin Mohamad Noor; Binti Mohamad, Zaleha (Research Progress in Mechanical and Manufacturing Engineering, 2022)
Bamboo or its scientific name Bambusoideae, Bamboos are a complex genus of evergreen perennial flowering plants that belong to the Poaceae grass family's Bambusoideae subfamily. It could be the country’s next industrial crop based on research findings on the technical and commercial potentials of the plant in Malaysia. These raw materials can be processed into pulp and paper, bio-composites for automotive door trimmings and interior shelving’s, as well as building material. Its specialty is having good mechanical properties and makes it desirable fibres in various industries. However, the application of bamboo as energy absorption by being the filler inside hollow cylindrical tube structure has not been much explored. In this study, quasi-static simulation study using finite element program, ABAQUS has been carried out on empty and bamboo foam composite filled in hollow cylindrical tube with three different of wall thickness and four different percentages of bamboo particle. Wall thickness that has been used are 2.5mm, 3.2mm and 4.0mm, while densities of 5%, 10%, 15% and 20% bamboo particle is used to develop the model of material. Simulation studies were conducted to obtain the mechanical properties and from the simulation result, the mechanical performance of loaded tubes can be improved by adding foam fill compared to increasing the wall thickness of the cross section. The energy absorption can be determined for the whole model and also for all elements or nodes. Energy absorption capability is proportional to the wall thickness. When the wall thickness is increased, energy absorption also increased. This situation is not same with the increasing the bamboo foam density. For the effect of adding the bamboo density, energy absorption increases from 5% until 10%, and then become decrease slightly until 20%. This study showed that optimum energy absorption can be obtained by increased the wall thickness and bamboo foam filler.